A study on factors influencing employee’s job satisfaction at Platinum Green Chemicals Sdn. Bhd. / Sharifah Solehah Syed Amiludin and Shara Nor Atikah Shamsuddin - Syed Amiludin, Sharifah Solehah; Shamsuddin, Shara Nor Atikah (2014)
Job satisfaction reflects an individual’s affective and emotional assessment of his or her work and interpreted by employee’s attitudes. Employee’s attitude typically reflects the moral of the company. Job satisfaction has its impact on the general life of the employees because satisfied employees are a contented and a happy human being and also will become happy employees. Job satisfaction is influenced by various psychological and environment factors. This paper aims to discover factors influencing employee’s job satisfaction at Platinum Green Chemicals Sdn. Bhd. While the problem statement in this study is the grievances of employee’s at Platinum Green Chemicals Sdn. Bhd.. The objective of this study are to identify the significant correlation between organizational justice and employee’s job satisfaction and to identify the significant correlation between organizational learning culture and employee’s job satisfaction at Platinum Green Chemicals Sdn. Bhd.. This research studied on two factors that influence employee’s satisfactions which are organizational justice and organizational learning culture. A research study questionnaire was administered to 152 participants at Platinum Green Chemicals. The results have been analysed. The study concludes that there is a positive relationship between organizational justice and employee’s job satisfaction and also there is a positive relationship between organizational learning culture and employee’s job satisfaction.